2018
DOI: 10.2217/rme-2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Mesenchymal Stem Cells in Treatment of Urinary Incontinence: a Systematic Review on Animal Models

Abstract: Aim: In recent years, the administration of stem cells has been considered a new option for treatment of urinary incontinence (UI). In the present study, the efficiency of mesenchymal stem cell (MSC) transplantation in the treatment of UI was evaluated. Methods: Combinations of the key words ‘mesenchymal stem cells’, ‘MSCs’, ‘urinary incontinence’, ‘urethral sphincter’ and ‘involuntary urination’ were searched in PubMed and Science Direct databases. Following application of exclusion criteria to the 1946 paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It was not ruled out that the transplantation of mesenchymal MSCs leads to neovascularization and restoration of muscle cells in animal models of incontinence via the paracrine process [ 12 ] or through the exosome production [ 23 , 24 ].…”
Section: Msc Incontinence Correction In Experimental Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not ruled out that the transplantation of mesenchymal MSCs leads to neovascularization and restoration of muscle cells in animal models of incontinence via the paracrine process [ 12 ] or through the exosome production [ 23 , 24 ].…”
Section: Msc Incontinence Correction In Experimental Modelsmentioning
confidence: 99%
“…Various types of MSCs have been investigated for use in the repair of the external sphincter and striated muscle tissue of the urethra. The use of MSCs appears to be a feasible and safe method with promising results for treatment of patients with incontinence [ 4 , 6 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Larsson et al found that isolated cloned human urothelial cells can self-renew in vitro and fully differentiate in vivo [14]. In addition, there have been multiple studies investigating the effects of mesenchymal stem cells on neovascularization and the recovery of urinary incontinence [15,16]. In 2019, we successfully localized and isolated female STM stem cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…New approaches are being considered to improve the treatment, but its development is still uncertain (eg, 3D bioprinted muscle 16 or tissue engineering 17 ). Mesenchymal stem cells (MSCs) have demonstrated, in experimental models, safety and efficacy against urinary incontinence 18 . But not only MSCs have demonstrated their efficiency in experimental models; in recent years, the proteins secreted by MSCs are generating interesting expectations for the treatment of urinary incontinence 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have demonstrated, in experimental models, safety and efficacy against urinary incontinence. 18 But not only MSCs have demonstrated their efficiency in experimental models; in recent years, the proteins secreted by MSCs are generating interesting expectations for the treatment of urinary incontinence. 19,20 Numerous safety clinical trials have also been developed to analyze the safety of different MSCs for the treatment of urinary incontinence 21 ; unfortunately, there are many differences between cellular origin, application system, and follow-up.…”
mentioning
confidence: 99%